EVALUASI KANDUNGAN MUTU FISIK DAN KIMIA SUSU SAPI PERAH FRIESIAN HOLSTEIN DI BPPIB TSP BUNIKASIH - Raden Febrianto Christi; Didin S Tasripin; Haykal Fathurrahman Elfakhriano (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2022)
Fresh milk that is good for consumption in terms of nutritional content and food safety must meet the applicable SNI. The quality of milk is largely determined by the components of substances contained in milk, including knowing the physical quality and chemical nutrient content. Research on Evaluation of Physical and Chemical Quality Content of Friesian Holstein Dairy Cows at BPPIB TSP Bunikasih was carried out in April-May 2021. The purpose of this study was to determine the physical quality of milk (color, flavor, taste, and specific gravity) and chemicals (fat, protein, and lactose) in first and second lactation FH cattle. This study uses a survey method with quantitative descriptive data analysis. The results showed that the physical quality of milk in the first lactation was yellowish-white, the characteristic flavor of milk, the sweet taste of milk, the density (BJ) of milk was 1.023 g/ml, the chemical quality of cow's milk in the first lactation was 4.86% fat content, protein 2.57%, and lactose 3.85% higher than lactation two on the physical quality of yellowish-white, distinctive aroma of milk, sweet taste of milk, density (BJ) 1.022 g/ml, the chemical quality of cow's milk in the second lactation, the fat is 4.67%, protein is 2.49%, and lactose is 3.73%. The conclusion of this study is the quality of milk in lactation one is higher than in lactation two. The physical quality of breast milk on density (BJ) still does not meet the Indonesian National Standard. The chemical qualities of milk are fat, protein, and lactose. The fat content of milk in each lactation has met the requirements of meeting the 2011 SNI, while the protein and lactose content of milk contained in BPPIB TSP Bunikasih is still below the 2011 SNI standard.